Penyebab Menurunnya Putaran Mesin Induk Mengakibatkan Tidak Maksimal Kinerja Mesin Induk No 2 pada Kapal - Sulthan Ghifari Rizqullah Junaidy (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Abstract. turbocharger is a vital component in many modern engines, which functions to increase engine performance and efficiency by compressing the air entering the combustion chamber. However, turbochargers often face various technical problems, one of which is damage to the turbo rotation. The purpose of this research is to discuss reducing RPM on ships to align research objectives, find out the problems that occurred during research, research objectives, problem formulation and research questions. This research method uses the qualitative type TSHD Rsa Marine 3 and the officers' efforts to take action when the main engine experiences a decrease in RPM, namely replacing components that affect the decrease in RPM such as replacing turbo components and air filters. This research was conducted using qualitative research methods, observation, interviews and related heritage. with a sudden drop in RPM. then take data such as RPM reduction statistics and pictures of component repairs that have a big influence on the reduction in Main Engine RPM. Based on the research results, it was concluded that the decrease in RPM was caused by damage to the compressor wheel and dirty turbo filter which resulted in abnormal RPM ME No. 2 on the ship.